TEACHERS' LESSON PLAN DEVELOPMENT IN ACCORDANCE WITH THE 2013 CURRICULUM AND ITS IMPLEMENTATION : A Case Study of Teaching Reading and Writing - Intan, Septia Latifa (2018)
The aims of this study were on analyzing English teachers' lesson plans to ensure whether or not the implementations were in line with lesson plan in classroom practice and whether or not the lesson plans had met the demand of the 2013 Curriculum. The study employed a qualitative research design by applying descriptive study as its framework, which was conducted in three different senior high schools in Bandung. The study involved three teachers, who were previously experienced in the 2013 Curriculum's training or workshop, seminar/conference based on the topic of curriculum, and MGMP (teachers' forum). All data were collected from document analysis, three times non-participant classroom observations and semi structure interview. There are two findings obtained in this study. Firstly, the data from teachers' lesson plans triangulated with interview data revealed that the teachers employed Systematic Planning Model in developing the lesson plan and fulfilled all elements of the lesson plan as suggested by the Regulation of Ministry of Education and Culture No. 22/2016 and 23/2016. However, the main problem teachers encountered was that they could not provide three learning domains evenly, in which the main focus was mostly on cognitive domain. Secondly, observational data showed that from five stages of scientific approach suggested by the 2013 Curriculum, two out of three teachers had succeeded presented in the classroom to some extent, as they needed to improve their knowledge in applying questioning and associating. The findings above suggest that the teacher needs more enhancement and guidance in developing lesson plan as well as a commitment and awareness to provide an effective teaching and learning process.;---Penelitian ini bertujuan menganalisa rencana pembelajaran guru bahasa Inggris untuk memastikan apakah RPP yang telah dirancang telah sesuai dengan tuntutan Kurikulum 2013 atau tidak dan apakah RPP yang dikembangkan telah sesuai dengan implementasinya di kelas. Penelitian ini menggunakan design penelitian qualitatif sebagai dasar penelitian, yang dilakukan di tiga SMA (Sekolah Menengah Atas) di Bandung. Studi ini melibatkan tiga guru yang sebelumnya mempunyai pengalaman dalam pelatihan maupun workshop Kurikulum 2013, seminar ataupun conference dengan tema kurikulum, dan bergabung dalam forum guru MGMP (Majelis Guru Mata Pelajaran). Seluruh data dalam penelitian ini dikumpulkan melalui analisis dokumen, observasi, dan wawancara. Hasil penelitian dalam studi ini mengungkapkan ada dua temuan. Pertama, data yang didapatkan dari dokumen RPP yang bertriangulasi dengan data interview menunjukkan bahwa guru-guru menggunakan Systematic Planning Model dalam mengembangkan RPP dan guru-guru juga menyatakan semua elemen rencana pelajaran sesuai dengan persyaratan yang tercantum dalam Peraturan Menteri Pendidikan dan Kebudayaan Nomor 22 tahun 2016 dan 23 tahun 2016. Akan tetapi, masalah utama yang dihadapi oleh guru adalah mereka tidak dapat memunculkan tiga tahapan pembelajaran secara seimbang, yang mana fokus pembelajaran hanya dititikberatkan pada aspek pengetahuan. Kedua, data observasi mengungkapkan bahwa dari lima activitas dalam pendekatan sainstifik yang tercantum dalam Kurikulum 2013, hanya dua dari tiga guru yang berhasil menerapkannya di dalam kelas dalam tingkatan tertentu, yaitu mereka disarankan untuk meningkatkan kemampuan mereka dalam activitas menanya (questioning) dan mengasosiasikan (associating). Penelitian ini menyimpulkan bahwa guru-guru butuh lebih banyak peningkatan dan bimbingan dalam mengembangkan RPP, maupun komitmen dan kesadaran untuk terus berusaha menfasilitasi siswa dengan proses belajar mengajar yang efektif.